Identificación de factores motivacionales y segmentos de emprendedores: sector turístico de Manta, Manabí - Flores de Valgas Zambrano, María Belén (2023)
The purpose of this research was to identify the motivational factors that contribute to the development of the segments of entrepreneurs in the tourism sector in Manta. The research is exploratory, non-experimental, with a qualitative-quantitative approach, and proposed a methodological design that consists of three phases. In the first, a characterization of the tourist enterprises was carried out, where the general characterization sheet was applied, interviews with main entities of the canton such as GADs, Chamber of Commerce, entrepreneurs, among others. Then, a strategic analysis of the enterprises in Manta Canton was made, the findings showed some weaknesses such as the deficient implementation of the regulations, little promotion of the tourist offer, low interest in training, etc. In the second one, the typology of tourist establishments was determined, to classify them and carry out a multidimensional analysis for this, 151 surveys were applied to the owners of the enterprises, where it was evidenced that new businesses or those already established, must work together with the GAD to improve the tourist offer and thus meet the needs of the tourist. In the last phase, the entrepreneurs were segmented, determining their profile and the motivational factors that affect them when starting their business idea through the information processed in SPSS to perform multivariate statistical analysis, cluster analysis, etc. Which gave as a result that the main motivational factors are culture-inheritance that belongs to millennials with 43.7% and employment-wealth that belongs to non-millennials with 56.3%.